Towards innovation-led growth-economic strategies leading Vietnam to higher-income status. - Cameron, Alicia (Lucy); Hien, Pham Thu; Giang, Nguyen Hoang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Vietnam has made remarkable economic advancement over the last 40 years to become a lower-middle income country with high rates of inclusive growth. The path for Vietnam from lower middle-income status to high-income status however will not be easy. Economic advancement will require a shift in focus to enhancing total factor productivity. The research supports the theory that the greatest economic gains in Vietnam can be made through technology adoption and adaptation, especially with one that encourages innovative activities to apply digital technology such as AI, robotics, platforms, the Internet of Things, AR/VR and blockchain, through education, infrastructure investment and ensuring the security of the digital networks rather than investing in the development of leading new technologies in the world. New technology research and development activities will be suitable for the development phase alongside the development of the legal corridor as well as the appropriate infrastructure. As Vietnam further develops, there will need to be another carefully timed switch in economic and investment strategy in order to become an innovation-led economy: one invests heavily in developing new technology, creates new industry sectors and exports knowledge-intensive products and services. Keywords: <em style="color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">20091801